2021
DOI: 10.3390/s21062105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Ability of Multi-Sensor Techniques to Capture Topographic Complexity

Abstract: This study provides an evaluation of multiple sensors by examining their precision and ability to capture topographic complexity. Five different small unmanned aerial systems (sUAS) were evaluated, each with a different camera, Global Navigation Satellite System (GNSS), and Inertial Measurement Unit (IMU). A lidar was also used on the largest sUAS and as a mobile scanning system. The quality of each of the seven platforms were compared to actual surface measurements gathered with real-time kinematic (RTK)-GNSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The targets we used had no marks at the center point where RTK-GNSS measurement is carried out, meaning that the target geolocation in the images can be prone to large horizontal uncertainties. The targets have been upgraded recently to include a chequerboard-like pattern, which has been recommended for pinpoint accuracy in RTK-GNSS measures and image positioning [71]. Nevertheless, we showed that error evaluation using ground targets can produce optimistic estimates, particularly when the error is evaluated at GCPs (used for photogrammetric processing).…”
Section: Discussionmentioning
confidence: 94%
“…The targets we used had no marks at the center point where RTK-GNSS measurement is carried out, meaning that the target geolocation in the images can be prone to large horizontal uncertainties. The targets have been upgraded recently to include a chequerboard-like pattern, which has been recommended for pinpoint accuracy in RTK-GNSS measures and image positioning [71]. Nevertheless, we showed that error evaluation using ground targets can produce optimistic estimates, particularly when the error is evaluated at GCPs (used for photogrammetric processing).…”
Section: Discussionmentioning
confidence: 94%
“…Georeferencing was prioritised on control points in images where targets were centrally located to reduce edge distortions. There is uncertainty on the optimal camera calibration corrections for SfM surveys processed in MS due to variations in sensor capabilities and pre‐processing of JPEGs for geometric adjustments (Bertin et al, 2022; Cooper et al, 2021; Gonçalves et al, 2021; Senn et al, 2022). Camera optimisation parameters or internal orientation parameters (Table 7) were chosen after extensive testing and according to works using a similar sensor (Cooper et al, 2021; Zhou, Daakir, et al, 2020).…”
Section: Study Sitesmentioning
confidence: 99%
“…Designated calibration targets placed in a controlled environment can be used to compare the performance of bulk measurement with both technologies in the future. A terrestrial laser scan (TLS) of the test site was performed separately [57], where a Leica ScanStation P40 with a 3 mm (1 𝜎) accuracy at 50 m was used. In this validation of the test site, the TLS point cloud was used as a true reference for the comparison with a vertical profile of down-sampled UAS-LIDAR point cloud collected on the rock stairs at the test site.…”
Section: Test Site Bulk Measurementsmentioning
confidence: 99%